ISOLATION OF BACTERIA CAUSING DENTAL CARIES FROM THE CLINICS OF THE COLLEGE OF BILAD AL-RAFIDAYN UNIVERSITY - Ahmed Qasim Abdulmahdi; Dumoua Latif Haram; Rasha Hadi Hassoun; Layla Salal Maktof; Hussein Ali Jassim; Ali Hussain Abd Alamir; Haneen Jumaa Ajeel; Hussein Abdelhassan Talab; Zahraa Ali Naji (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study deals with Isolation of bacteria causing dental caries from the Forty samples (male and female) were collected from patients attending the clinics of the Department of Dentistry at Bilad Al-Rafidayn University College for the period 7/11/2022 to 4/5/2023. The total of (58) isolates before and after cleaning and tooth extraction collected from male and female samples .After diagnosing these isolates, it was found that. Streptococcus (42.5%) and gram-negative (20%) before dental work and cleaning . The Percentage of Streptococcus after cleaning (30%) and the gram-negative rod (7.5%). The percentage of Streptococcus isolated from tooth extraction (20%) and staphylococcus (2.5%) and gram-negative rod(2.5%). The spacemen were collected from the oral cavity and the culture was on mitis salivarius(Himedia/India) agar base, that was determined by biochemical tests by use of blood agar to detect hemolysis, the results revealed the samples were positive.